PELATIHAN PEMANFAATAN NEARPOD SEBAGAI INOVASI PEMBELAJARAN DI SEKOLAH MI MUHAMMADIYAH PONOROGO - Wahyudi Wahyudi; Dwi Avita Nurhidayah; Sumaji; Dita Febriyanti (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Nearpod is a web-based media that can be accessed by anyone including teachers and students using a pre-owned gmail account. The presence of this nearpod provides a new color, especially for teachers in developing ideas and at the same time as learning innovations, especially mathematics. Science and technology for the community (IbM) by utilizing the nearpod is one of the community service activities (PkM), especially for MI Muhammadiyah teachers in Ponorogo as a new breakthrough to complete and provide convenience for teachers in providing material information and students easily accessing that information. This “nearpod” web media began to boom in 2020 until now, which adapts online learning activities (on the network). It is hoped that this activity will provide new information for teachers that the nearpod can be used as an innovation in mathematics learning in particular. Nearpod can support mathematical material that can be well designed, so that students will easily understand math material. In addition, with this new normal condition, of course there are still some things that are related to media that can be accessed by students at any time. From this activity, the teacher has been able to create and design learning materials with nearpods for mathematics materials.